Pendampingan dan Pemanfaatan Ekskul Karate dalam Meningkatkan Kebugaran Jasmani di SDIT AL Ghazali - Dina Rahmawati; Abdullah Abdullah (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2024)
Muslims were created by Allah in the best possible form. Maintaining God's creation can be done with various efforts, one of which is sports which are related to regulating emotions and diet to improve physical fitness. The healthier our body is, the more comfortable it is to worship Allah. Talking about physical education, which is commonly known as physical education, is closely related to health. Health is the most precious gift from Allah because of the blessings that are needed in a person's life, including in terms of worshiping Allah. Therefore, it is very important to maintain health through exercise that can improve body fitness. So if we relate it to extracurricular activities in school, we can see how karate is able to improve the physical fitness of karateka (people who follow karate) towards their worship of Allah with the target of students in elementary schools with various age ranges. Through the Asset Based Community Development (ABCD) method, conclusions can be drawn that the use of karate extracurricular can fit the body and have an impact on body health and focus on worshipping Allah. This theme is interesting to explore because it is still not paid attention to and applied in school life as well as in daily life. The hope is to make yourself aware of how important the level of fitness in the body is through karate extracurricular at school and also help make school institutions and coaches who have professional abilities in the field of karate proud